Effect of different flow schemes on heat recovery from Enhanced Geothermal Systems (EGS). (15th May 2019) - Asai, Pranay; Panja, Palash; McLennan, John; Deo, Milind
Abstract: Operational optimization is the key to maximize the heat extraction efficiency of Enhanced Geothermal Systems (EGS). Injection/production flowrate is one of the operational parameters that can be easily manipulated to produce desired amount of energy. In this study, the effect of different flow schemes on the rate of heat production is analyzed over a period of 30 years. Seven flow schemes (four continuous functions namely constant flow, linear flow, exponential flow, mirror exponential flow, and three step functions with step sizes of six months, three years and ten years) developed on the basis of mathematical functions were examined. A doublet EGS model with a single fracture was simulated using a commercial thermal reservoir simulator. The reservoir and well data were obtained from the FORGE (Frontier Observatory for Research in Geothermal Energy) site at Milford Utah. The results were analyzed on the basis of their temperature decline curves for the produced water and the total amount of heat extracted over the entire period. The exponential flow scheme is the optimum case considering the rise in energy demand over the next 30 years. The amount of heat extracted per unit volume of water decreases with increase in total water volume circulated. Highlights: A doublet well system based on data from the FORGE site near Milford, Utah, USA is studied. Seven different injection schemes are explored to optimize the heat recovery from EGS. Exponential flow is the optimized water injection scheme in maximizing heat recovery in 30 years. This study is useful for development and sustainable operation of geothermal power plant.